Are PD-1 inhibitors effective for recurrent/metastatic nasopharyngeal carcinoma? Meta-analysis and systematic review - Yan, Le; Ren, Bi; Hu, Rongqiu; Zhang, Huiping; Gou, Haocheng (Frontiers in Pharmacology, 2023)
Abstract Objective: For metastatic/recurrent nasopharyngeal carcinoma (NPC) patients, a programmed cell death protein 1 (PD-1) is a controversial option. This meta-analysis aimed to investigate the efficacy and safety of PD-1 inhibitors in patients with metastatic/recurrent NPC. Methods: Electronic databases such as PubMed, Embase, Cochrane library, and Web of Science were manually searched until July 1, 2022, and Stata 15.0 was used to analyze the data. Result: A total of 10 studies were included, of which 3 were randomized controlled trials with data, and 7 were single-arm studies. For randomized controlled trial (RCT) study, ORR [OR=1.11, 95%CI (0.49, 2.52); P= 0.812], OS [1-year OR=1.26, 95%CI (0.76, 2.08); P=0.367], [2-year OR=1.04, 95%CI (0.39, 2.71); P=0.928] in patients with metastatic/recurrent NPC were consistent with PD-1 inhibitor therapy and conventional chemotherapy. However, PD-1 inhibitor had higher 1-year PFS than conventional chemotherapy [OR=2.16, 95%CI (1.26, 3.70); P=0.005]. For single-arm studies, after PD-1 inhibitor therapy, the ORR of patients with recurrent/metastatic NPC reached [ES=37%, 95CI (17%-56%)], 1-year OS [ES=61%, 95%CI (46%-76%)], 2-year [ES=16%,95CI (6%-26%)], and 1-year PFS [ES=16%,95% CI (12%-20%)]. Conclusion: The efficacy of PD-1 inhibitor monotherapy in patients with metastatic/recurrent nasopharyngeal carcinoma was not significantly different from that of conventional chemotherapy; however, due to the limitations of the included studies, further phase III RCTs are required to corroborate our conclusion.